The Effects of Low-Level Laser Therapy, 670 nm, on Epiphyseal Growth in Rats - Adriana Regina de Andrade; Anamaria Meireles; Elisangela Lourdes Artifon; Rose Meire Costa Brancalhão; José Roberto Leonel Ferreira; Gladson Ricardo Flor Bertolini (The Scientific World Journal)
The longitudinal growth of long bones is attributed to epiphyseal growth. However, the effects of low-level laser therapy (LLLT) in such structures has still not been studied extensively in the literature. Therefore, the aim of this study was to evaluate the use of LLLT, 670 nm, at three different doses on the epiphyseal growth of the right tibia of rats. Twenty-one Wistar rats, aged four weeks, were subjected to the application of LLLT, with dosage according to the group (G4: were submitted to the application of 4 J/cm2; G8: were submitted to the application of 8 J/cm2; G16: were submitted to the application of 16 J/cm2). After completion of protocol they were kept until they were 14 weeks of age and then submitted to a radiological examination (evaluation of limb length) and euthanised. The histological analysis of the growth plates (total thickness and hypertrophic and proliferative zones) was then performed. Comparisons were made with the untreated left tibia. No differences were observed in any of the reviews (radiological and histological), when comparing the right sides (treated) to the left (untreated). It was concluded that the treatment with LLLT within the parameters used caused changes neither in areas of the epiphyseal cartilage nor in the final length of limbs.